Citizen attitudes toward crime and punishment: a pilot study at EAFIT , Medellín University (2013)
In order to justify an expansionist criminal policy, it is usual to appeal to the fact that this one responds to the popular claim, a social demand for security. However, current academic efforts in criminology have refuted this hypothesis. With wide empi